Post-Ablation Cavity Evaluation: A Prospective Multicenter Observational Clinical Study to Evaluate Hysteroscopic Access to the Uterine Cavity 4 Years After Water Vapor Endometrial Ablation for the Treatment of Heavy Menstrual Bleeding. Issue 1 (January 2021) - Johns, D. Alan; Garza-Leal, Jose G.; Diamond, Michael P.; Harris, Micah
Abstract : (Abstracted from J Minim Invasive Gynecol 2020;27:1273–1280) A minimally invasive treatment for heavy menstrual bleeding (HMB) due to benign causes in women who have completed childbearing is endometrial ablation (EA). Intracavity scarring following EA may result in recurrent heavy bleeding, cyclic pelvic pain with or without bleeding, and postmenopausal bleeding, often manifesting many years after the original treatment.